2017
DOI: 10.1371/journal.pone.0190293
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the thickness of the crestal and buccolingual cortical bone at varying depths and implant stability quotients

Abstract: Background/purposeResonance frequency analysis (RFA) is clinically used in dentistry to access the stiffness of dental implants in surrounding bone. However, the clear advantages and disadvantages of this method are still inconclusive. The aim of this study was to investigate and compare implant stability quotient (ISQ) values obtained from RFA with parameters obtained from a cone beam computed tomography (CBCT) scan of the same region.Materials and methodsNineteen implants (Conelog) were inserted in the poste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…Therefore, the only factors that showed a positive correlation between the IT and the ISQ value were the bone density and thickness of the cortical bone. This result is in accordance with other publications [12,40]. Moreover, Lages et al reported that the clinician should choose only one of the methods to determine the primary stability of implants, as these are independent and incomparable methods [12].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the only factors that showed a positive correlation between the IT and the ISQ value were the bone density and thickness of the cortical bone. This result is in accordance with other publications [12,40]. Moreover, Lages et al reported that the clinician should choose only one of the methods to determine the primary stability of implants, as these are independent and incomparable methods [12].…”
Section: Discussionsupporting
confidence: 90%
“…Bone width near the alveolar bone crest is generally assessed to select proper implant size and insertion site based on the available bone so that the bone surrounding the inserted implant could be well preserved, resulting in good primary implant stability [23]. While cortical bone thickness also correlates with the implant primary stability [24,25], we included the parameters such as bone condition since it plays a role in successful dental implant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The table further describes Misch’s classification for bone types in edentulous ridges according to the different areas of the maxilla and mandible, as well as Chatvaratthana et al’s. [ 6 ] quantitative bone classification for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…These qualitative classifications can be further extended, and to some extent quantified, by considering the ratio between cortical to cancellous bone volume, as assessed in a routine CT scan. In that spirit, Chatvaratthana et al [ 6 ] reported that a ratio in excess of 0.75 (75–100% cortical bone) corresponds to D1 bone type, 0.5–0.75 (50–75% cortical bone) to D2 bone type, 0.25–0.5 (25–50% cortical bone) to D3 bone type and D4 bone type contains less than 0.25 (0–25% cortical bone). This classification does not take into consideration the total bone volume and does not differentiate between the different areas of the maxilla and the mandible.…”
Section: Introductionmentioning
confidence: 99%